2023
DOI: 10.21037/qims-22-307
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial volumes and strains in healthy adults: is the Frank-Starling mechanism working?—detailed analysis from the three-dimensional speckle-tracking echocardiographic MAGYAR-Healthy Study

Abstract: Background: With larger blood volume flowing into a cardiac chamber, by stretching muscle fibers, increased contraction force could be detected. This phenomenon is called Frank-Starling mechanism, allowing the output of a cardiac chamber to be synchronized without external regulation. The purpose of the present study was to investigate the Frank-Starling mechanism in the right atrium (RA) represented by its volumes, volume-based functional properties and strains respecting the cardiac cycle in healthy adults b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, transmural fiber angle distribution is heterogeneous throughout different regions of the atria, which could partially explain why associations with RA-LS and RA-CS could not be detected [ 23 ]. In a recent study, the Frank–Starling mechanism for RA was examined and demonstrated that increasing RA volumes do not cause a significant increase in peak RA strains representing reservoir function in systole [ 11 ]. This finding was extended in this study, demonstrating that increased RA contractility in longitudinal direction represented by peak RA-LS is associated with larger V max and lower V min .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, transmural fiber angle distribution is heterogeneous throughout different regions of the atria, which could partially explain why associations with RA-LS and RA-CS could not be detected [ 23 ]. In a recent study, the Frank–Starling mechanism for RA was examined and demonstrated that increasing RA volumes do not cause a significant increase in peak RA strains representing reservoir function in systole [ 11 ]. This finding was extended in this study, demonstrating that increased RA contractility in longitudinal direction represented by peak RA-LS is associated with larger V max and lower V min .…”
Section: Discussionmentioning
confidence: 99%
“…ECG, 2DE, and 3DSTE showed results in the normal reference ranges. The present study is part of the M otion A nalysis of the heart and G reat vessels b Y three-dimension A l speckle-t R acking echocardiography in Healthy subjects (MAGYAR-Healthy) Study aiming to investigate physiological relationships among 3DSTE-derived and other parameters in healthy adults (’Magyar’ means ’Hungarian’ in the Hungarian language) [ 8 , 9 , 10 , 11 ]. The study was conducted in accordance with the Declaration of Helsinki (as revised in 2013, and the updated versions).…”
Section: Methodsmentioning
confidence: 99%
“…Not only is the spread of cardiac magnetic resonance imaging and computer tomography observed, but new echocardiographic procedures have appeared as well. STE is one of the most recent developments, which can see and visualize the heart and its cavities, including both atria, using 3D models [7,8,10,11]. Three-dimensional speckle-tracking echocardiography is suitable for detailed atrial volumetric and volume-based functional analysis using SVs and EFs, respecting the cardiac cycle [7,8,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional speckle-tracking echocardiography-derived data acquisitions were done immediately after complete 2D echocardiography, according to recent guidelines and practices. The present retrospective cohort study is part of the 'Motion Analysis of the heart and Great vessels bY three-dimensionAl speckle-tRacking echocardiography in Healthy subjects' (MAGYAR-Healthy) Study, which was organized at the University of Szeged for the purpose of carrying out physiological clinical studies ('Magyar' means 'Hungarian' in Hungarian language) [1,8,[10][11][12]. The study was conducted in accordance with the Declaration of Helsinki (as revised in 2013).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation